CT Findings in Patients with COVID-19-Compatible Symptoms but Initially Negative qPCR Test - Valentin, Birte; Steuwe, Andrea; Wienemann, Tobias; Andree, Marcel; Keitel, Verena; Ljimani, Alexandra; Appel, Elisabeth; Köhler, Marie-Helen; Rademacher, Christin; Antoch, Gerald; Aissa, Joel (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2022)
Purpose To assess whether it is possible to reliably detect patients with strong suspicion of COVID-19 despite initially negative quantitative polymerase-chain-reaction (qPCR) tests by means of computed tomography (CT).Materials and Methods 437 patients with suspected COVID-19 but initially negative qPCR and subsequent chest CT between March 13 and November 30, 2020 were included in this retrospective study. CT findings were compared to results of successive qPCR tests (minimum of 3 qPCR tests if CT suggested infection) to determine the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of CT for diagnosing COVID-19.Results COVID-19 was diagnosed correctly with a sensitivity of 100 % [95 % confidence interval (CI): 65–100] and a specificity of 88 % [95 % CI: 84–90]. A PPV of 12 % [95 % CI: 6–22] and an NPV of 100 % [95 % CI: 99–100] were determined.Conclusion CT is able to detect COVID-19 before qPCR in initially negative patients in this special study setting. Similar CT findings in COVID-19 and other atypical pneumonias can lead to high numbers of false-positive patients, reducing the specificity of CT.Key Points: Citation Format
Keywords: quantitative PCR; pneumonia, viral; SARS-CoV-2; SARS-associated coronavirus; multidetector computed tomography